HO-1 Induction Improves Type-1 Cardiorenal Syndrome in Mice with Impaired Ang II-induced Lymphocyte Activation (SCID Mice) - Monu, Sumit R. (2013)
Type-1 cardiorenal syndrome (CRS-1), characterized by acute kidney dysfunction secondary to cardiac failure and renal arteriolar vasoconstriction, is mediated by the renin-angiotensin-aldosterone axis and sympathetic nervous system activation. Previous reports indicate that AngII modulates immune function and causes recruitment and activation of T lymphocytes. The goal of this study was to evaluate the effects of post-ischemic heart failure on renal morphology and circulation and the beneficial effects of heme oxygenase (HO-1) induction in T- lymphocyte suppressed BALB SCID mice. Mice were divided in 4 groups: sham, myocardial infarction (MI), MI treated with an HO-1 inducer, cobalt protoporphyrin (CoPP), and with or without stannous mesoporphyrin (SnMP), an inhibitor of HO activity. Heart and kidney function were studied 30 days after surgery. Fractional area change was reduced 30 days after surgery in both the C57 and SCID MI-groups as compared to their respective controls (p<0.01). Renal pulsatility index and renal injury were increased in C57 and SCID MI groups compared to the sham group. HO-1 induction improved renal vasoconstriction as well as ameliorated renal injury in both the SCID and C57 MI groups (p<0.01). However, improvement was more evident in SCID mice. In addition, our results showed that plasma creatinine, Ang II and renin were significantly increased in the C57 and SCID MI groups as compared to their respective controls. HO-1 induction decreased these parameters in both MI groups. SnMP reversed the beneficial effect of CoPP in both mouse strains. The study demonstrates that T-lymphocyte suppression facilitated the HO-1 dependent improvement in the attenuation of CRS-1.